2016
DOI: 10.1016/j.amepre.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Referring Hospitalized Smokers to Outpatient Quit Services

Abstract: Introduction Linking outpatient cessation services to bedside counseling for hospitalized smokers can improve long-run quit rates. Adding an assisted referral (AR) offer to a tobacco treatment specialist consult service fits the team approach to care in U.S. hospitals. Design A two-arm patient-randomized trial tested the effectiveness of adding an AR offer to outpatient smoking-cessation services and interactive voice recognition (AR+IVR) follow-up to a usual care (UC) tobacco-cessation consult for hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
0
14
0
3
Order By: Relevance
“…Multicomponent interventions for inpatient smoking cessation are widely encouraged by best-practice guidelines ( Fiore et al 2000 ;West et al ;Global Initiative for Chronic Obstructive Lung Disease 2015 ;Yang et al 2016 ). Most studies found in this review evaluated a bedside counselling program combined with NRT and post-discharge telephone and/or outpatient cessation support.…”
Section: Multicomponent Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multicomponent interventions for inpatient smoking cessation are widely encouraged by best-practice guidelines ( Fiore et al 2000 ;West et al ;Global Initiative for Chronic Obstructive Lung Disease 2015 ;Yang et al 2016 ). Most studies found in this review evaluated a bedside counselling program combined with NRT and post-discharge telephone and/or outpatient cessation support.…”
Section: Multicomponent Interventionsmentioning
confidence: 99%
“…One can provide face-to-face counselling ( Lancaster and Stead 2005 ) or can refer to a telephone counselling service , hereafter referred to as a Quitline. Alternatively, there are a number of smoking cessation medications that can assist during a quit attempt, including varenicline tartrate (varenicline) ( Ebbert et al 2010 ;Cahill et al 2013 ), bupropion hydrochloride (bupropion) ( Raupach and van Schayck 2011 ;Cahill et al 2013 ) or nicotine replacement therapy (NRT) ( Ferguson et al 2011 ;Cahill et al 2013 ). Combining pharmacotherapy and counselling, hereafter referred to as a multicomponent strategy, is an additional option, which has been shown to increase quit rates from 10 to 25 percent compared to pharmacotherapy alone ( Stead and Lancaster 2012 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Providing smoking cessation medications for patients as an adjunct to counseling significantly improves long term quit rates (Fiore et al, 2008). A number of studies have examined methods for implementing these two elements of care into hospital treatment and post-discharge care planning (Sherman et al, 2016; Rigotti et al, 2016; Rigotti and Stoney, 2016; Richter et al, 2016; Harrington et al, 2016; Fellows et al, 2016; Duffy et al, 2016; Cummins et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…4 However, only 1% of tobacco users use Quitlines. 4 The Consortium of Hospitals to Advance Research on Tobacco (CHART) studies reported mixed results on effectiveness of Quitline fax-referral [5][6][7][8][9][10] and concluded that engaging tobacco users in post-discharge treatment is a challenge. 3 We implemented and evaluated a systems-based approach for inpatient tobacco cessation that utilized trained bedside volunteers with the goals of Quitline referral and tobacco cessation.…”
Section: Introductionmentioning
confidence: 99%